The Ability Of The Sickle Kick Speed Of Pencak Silat Athletes - Jeki Haryanto; Ambi Mayu; Juanda Putra; Suci Nanda Sari (STAMINA, 2026)
The speed of the sickle kick is one of the fundamental technical components that is very important in pencak silat in the competition category, where the ability to make a kick quickly and accurately determines the success of the athlete in scoring points and winning the match. The problem in this study is the lack of the ability to kick the speed of the sickle kick in pencak silat athletes of Pat Ban Bu Padang College, which has an impact on the achievement of optimal achievements in competitions. This study aims to find out and analyze the speed of the sickle kick of pencak silat athletes of Pat Ban Bu Padang College. The type of research used is quantitative descriptive research with a survey approach. The population in this study is all pencak silat athletes of Pat Ban Bu Padang College which totals 20 people. The sampling technique used total sampling, so that the entire population of 20 people was used as a research sample. The instrument used in this study is a sickle kick speed test which measures the number of kicks an athlete can make in a given period of time. The data analysis technique uses descriptive statistics with percentage calculation and categorization based on predetermined assessment norms. The results of the study showed that the ability of the scythe kick speed of pencak silat athletes of Pat Ban Bu Padang College was mostly in the good category (70%), the very good category (20%), and the medium category (10%). Based on these findings, it is recommended that coaches develop a more systematic and structured training program with a focus on improving the biomotor components that support kick speed such as leg muscle power, flexibility, and coordination, as well as paying special attention to athletes in the medium category through a more intensive remedial training program.